2014
DOI: 10.1007/s00262-014-1603-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a cytotoxic T-lymphocyte agonist epitope of brachyury, a transcription factor involved in epithelial to mesenchymal transition and metastasis

Abstract: The transcription factor brachyury is a major driver of epithelial to mesenchymal transition (EMT) in human carcinoma cells. It is overexpressed in several human tumor types vs. normal adult tissues, except for testes and thyroid. Overexpression is associated with drug resistance and poor prognosis. Previous studies identified a brachyury HLA-A2 cytotoxic T-lymphocyte (CTL) epitope. The studies reported here describe an enhancer epitope of brachyury. Compared to the native epitope, the agonist epitope: (a) has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
2

Relationship

5
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…Utilizing 9-mer peptides of the brachyury protein, for example, brachyury-specific CD8 + T cells have been expanded in vitro from the blood of cancer patients. These brachyury-specific CD8 + T cells were utilized in cytotoxic assays for effective lysis of human tumor cells that endogenously express brachyury (23,24). These combined properties, i.e., tumor-restricted expression, relevant function in tumor progression, and immunogenicity, make the self-antigen brachyury a potential target for immunotherapy-mediated approaches against cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing 9-mer peptides of the brachyury protein, for example, brachyury-specific CD8 + T cells have been expanded in vitro from the blood of cancer patients. These brachyury-specific CD8 + T cells were utilized in cytotoxic assays for effective lysis of human tumor cells that endogenously express brachyury (23,24). These combined properties, i.e., tumor-restricted expression, relevant function in tumor progression, and immunogenicity, make the self-antigen brachyury a potential target for immunotherapy-mediated approaches against cancer.…”
Section: Introductionmentioning
confidence: 99%
“…NK cells were isolated from healthy donor peripheral blood mononuclear cells by using a magnetic NK Cell Isolation Kit (Miltenyi Biotech) and were cultured in RPMI media containing 10% FBS. Antigen-specific, HLA-A 02 -and HLA-A 24 -restricted cytotoxic T lymphocytes directed against an epitope of brachyury (WLLPGTSTV) or mucin-1 (MUC-1, KYHPMSEYAL), respectively, were generated and expanded as previously described from the blood of cancer patients (80)(81)(82).…”
Section: Chemotaxis Assay Cd11bmentioning
confidence: 99%
“…It has been previously shown that brachyury is immunogenic in humans [12, 35, 36] and based on those studies, a heat-killed recombinant Saccharomyces cerevisiae (yeast) brachyury vaccine and a MVA-poxviral vaccine encoding brachyury and a triad of costimulatory molecules (TRICOM) have been developed and characterized [26] and entered Phase I clinical testing in patients with advanced carcinomas or chordomas [28, 29, 37, 38]. In the context of clinical studies of brachyury-based vaccines, we believe MAb 54-1 could be of potential use to determine what type of tumors express brachyury and could therefore be targets, and to evaluate the presence of brachyury-positive tumor cells pre vs. post-treatment, therefore assisting in the interpretation of the efficacy of brachyury-based therapies.…”
Section: Discussionmentioning
confidence: 99%